2018
DOI: 10.1017/s1047951118001397
|View full text |Cite
|
Sign up to set email alerts
|

2D-Speckle tracking echocardiography contributes to early identification of impaired left ventricular myocardial function in children with chronic kidney disease

Abstract: The study concluded that 2D-speckle tracking echocardiography method can determine cardiac involvement earlier than conventional echocardiography in children with chronic kidney disease having preserved ejection fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Actually, long‐term reduced perfusion can lead to progressive fibrosis and decreased myocardial deformability. 2D‐STE enables the sensitive detection of subtle changes in myocardial deformation 18–20 . It can track the hyperechoic spots of myocardial tissue from a ROI within the 2D grayscale image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, long‐term reduced perfusion can lead to progressive fibrosis and decreased myocardial deformability. 2D‐STE enables the sensitive detection of subtle changes in myocardial deformation 18–20 . It can track the hyperechoic spots of myocardial tissue from a ROI within the 2D grayscale image.…”
Section: Discussionmentioning
confidence: 99%
“…2D-STE enables the sensitive detection of subtle changes in myocardial deformation. [18][19][20] It can track the hyperechoic spots of myocardial tissue from a ROI within the 2D grayscale image. Migrino et al 21 have confirmed that 2D-STE is superior to the conventional B-mode and M-mode ultrasonography in the detection of myocardial ischemia by establishing a rat ischemia-reperfusion model.…”
Section: Discussionmentioning
confidence: 99%
“…Further, 25% of the deaths among patients younger than 30 years of age and 40% of all deaths occur due to cardiovascular disease. 1,2 The demonstration of subclinical cardiac dysfunction is therefore important in terms of increasing life expectancy by taking early preventive measures. The American Society of Echocardiography and the European Society of CKD therefore recommend the use of TDI in routine cardiac evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of these techniques is limited due to dependence on software, need for experience, lack of cost-effectiveness, and sedation. 2,30 The MPI is calculated by dividing the sum of the IVCT affected by systole and the IVRT affected by diastole by the ET affected by systole. The MPI is therefore used as an indicator of both systole and diastolic dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular complications are considered the most important causes of death in CKD patients. Whether these complications are related to endothelial dysfunction, pericardial disease, infective endocarditis from catheter related infections and last but not least myocardial dysfunction [10,11].…”
Section: Discussionmentioning
confidence: 99%